Research on passive localization method of shallow water acoustic source with single hydrophone based on hierarchical grid histogram filtering. (15th June 2022) - Shi, Haijie; Li, Jinghua; Chang, Hong; Liu, Lili
Highlights: The probability density function mode improves the method performance in complex environment. The iterative form algorithm realizes target location with a single hydrophone. The hierarchical grid design technology improves the efficiency of the algorithm. Abstract: An acoustic field model in the form of a probability density function is established to solve the problem of environmental instability in shallow water. A Bayesian underwater acoustic localization model with the state vector of the acoustic source as a posteriori probability is generated for the purpose of trading time for space in an iterative form and realizing localization of a moving source with a single hydrophone. A hierarchical grid histogram filtering algorithm is proposed, which solves the integral problem in the process of Bayesian filtering and improves the efficiency of the histogram filtering algorithm greatly. The SWellEx-96 experimental results show that in the range of 200 m * 10 km, the relative error of depth positioning is controlled at 12%, the relative error of distance positioning is controlled at 7%, and the efficiency of the algorithm is improved by N 1/2 times where N is the number of grids of the histogram filter. The method proposed in this paper is suitable for concealed and low energy consumption platforms in shallow water.